The Role of Housewives in Improving the Family Economy in Waiheru Village RW 004 - Sahira Ati, Siti; Sinay, Francisca Riconita; Louhenapessy, William George M (JENDELA PENGETAHUAN, 2025)
This study aims to analyze the role of housewives in improving the family economy in Waiheru Village, RW 004. Housewives play a crucial role in creating additional income sources through various economic activities, such as trading and running small businesses. Despite facing limitations in terms of capital and time, housewives in Waiheru have significantly contributed to enhancing family welfare. Based on interviews, housewives effectively manage their time between household duties and the businesses they run. Furthermore, support from husbands and other family members strengthens their role in the family's economy. Common challenges include physical fatigue; however, with high determination and innovation, housewives continue to fulfill both roles successfully. This study concludes that housewives possess substantial potential in family economic empowerment, yielding positive impacts on family welfare and strengthening the local economy.